Nilai Islam dan Nilai Kebangsaan dalam Pembelajaran Bahasa Indonesia - Siti Mutmainah (STAIFAS-Press, 2018)
ABSTRACT There are three basic patterns that can be developed in coaching imtaq and national values in school. First, imtak guidance through religious education and nationality through Civics education, as we have seen so far. Programs like this certainly have many weaknesses, because religious teachers and PK teachers are only independent. Second, integrating the values of Islam and nationality in each subject, while still making the teacher of religion and PK as central to the formation of imtaq and nationality. Third, is to empower all potential teachers to jointly develop the values of imtaq and nationality through the learning process in each field of study. This pattern has many advantages, because every teacher in the field of study has the same vision and mission. Keywords:IslamicValue, National Value, Indonesian Language